P10 Randomised Placebo Controlled Trial to Evaluate Chronic Dosing Effects of Propranolol in Steroid Treated Persistent Asthmatics. (19th November 2012) - Short, PM; Williamson, PA; Anderson, WJ; Lipworth, BJ
Abstract : Introduction and Objectives: Beta-blockers are associated with acute bronchospasm in asthmatics. However preliminary unblinded studies have shown potential therapeutic benefits with chronic beta-blockade on airway hyper-responsiveness (AHR) in steroid naïveasthmatics. We examined the effects on AHR of propranolol versus placebo in steroid treated persistent asthmatics. Methods: A double-blind randomised placebo controlled crossover trial of propranolol in mild-to-moderate asthmatics receiving inhaled corticosteroids (ICS) was performed (NCT01074853 ). Participants underwent a six to eight week dose titration of propranolol or placebo as tolerated to a maximum of 80mg per day. Tiotropium was given concurrently for the first four to six weeks of each treatment period. Primary outcome was methacholine challenge (without tiotropium). Secondary outcomes included histamine challenge (with and without tiotropium), pulmonary function, heart rate, blood pressure, mini-asthma quality of life questionnaire (mini-AQLQ) and asthma control questionnaire (ACQ). Results: 18 patients completed: mean (SEM); age 36 (4), FEV1% 93 (2), ICS ug/day 440 (66). No significant difference was observed in methacholine or histamine challenge following exposure to propranolol versus placebo. For methacholine challenge (without tiotropium) the doubling dilution difference (DDD) was 0·04 (95%CI –0·56 – 0·63), p=0·89. For histamine challenge without tiotropium the DDD was 0·42 (95%CI –0·09 – 0·93), p=0·10; and with tiotropium was DDD 0·26 (95%CI –0·36 – 0·87), p=0·39. Salbutamol induced chronotropic response was significantly blunted following propranolol versus placebo: mean difference 25bpm (95%CI 14 – 37), p<0·001. No difference was found for ACQ, mean difference 0·18 (95%CI –0·23 – 0·58), p= 0.79 or mini-AQLQ, mean difference 0.14 (95%CI –0·19 – 0·46), p=0·84. Conclusions: This is the first placebo controlled study to assess the effects of chronic non selective beta-blockade in steroid treated persistent asthmatics, showing no significant effect of propranolol compared to placebo on AHR to either methacholine or histamine and no change in ACQ or AQLQ.